Selenium uptake, tolerance and reduction in Flammulina velutipes supplied with selenite - Wang, Jipeng (PeerJ, 2016)
Recently, selenium (Se) enriched mushrooms have been exploited as dietary Se supplements, but our knowledge of the metabolic process during the Se enrichment process is far from complete. In this study, the uptake, tolerance and reduction of selenite in a widely cultivated mushroom, Flammulina velutipes, was investigated. The results showed that pH variation (from 5.5–7.5), metabolic inhibitor (0.1 mM 2,4-DNP) and P or S starvation led to 11–26% decreases in the selenite uptake rate of F. velutipes. This indicates that a minor portion of the selenite uptake was metabolism dependent, whereas a carrier-facilitated passive transport may be crucial. Growth inhibition of F. velutipes initiated at 0.1 mM selenite (11% decrease in the growth rate) and complete growth inhibition occurred at 3 mM selenite. A selenite concentration of 0.03–0.1 mM was recommended to maintain the balance between mycelium production and Se enrichment. F. velutipes was capable of reducing selenite to elemental Se [Se(0)] including Se(0) nanoparticles, possibly as a detoxification mechanism. This process depended on both selenite concentration and metabolism activity. Overall, the data obtained provided some basic information for the cultivation of the selenized F. velutipes, and highlighted the opportunity of using mushrooms for the production of Se(0) nanoparticles.